JUVENILE NASOPHARYNGEAL ANGIOFIBROMA: AN ENDOSCOPIC APPROACH WITH PRE-OPERATIVE EMBOLIZATION SUPPORTED BY NEURONAVIGATED COMPUTED TOMOGRAPHY - Cosimo Galletti (Euromediterranean Biomedical Journal, 2023)
The purpose of this clinical report is to present our surgery approach combined to the preoperative embolization and the follow-up management of a patient with a Juvenile Nasopharyngeal Angiofibroma (JNA). JNA is a relatively uncommon vascular benign neoplasm that affects almost exclusively adolescent males and represents 0.05% of all head and neck tumors with an incidence of 1:150,000. We present a case of a nineteen-year-old patient with severe and recurrent episodes of epistaxis in the last months. Nasal endoscopy showed a vascularized neoformation that obliterate the right posterior nasal cavity and rhinopharinx. A skull computed tomography (CT) study with contrast medium showed a three centimeters soft tissue mass within the right posterior nasal cavity with extension to the homolateral pterygopalatine fossa and adjacent sphenoid sinus; a little forward bowing of the posterior wall of the right maxilla (Holman–Miller sign) was reported. An angiographic exam was performed, in the same time, was carried out an embolization of intense vascular supply of the mass. We decided to perform an endoscopic approach supported by neuronavigated computed tomography to remove the mass. The advance in the endoscopic surgery approach in cases of such complexity with the support of a neuronavigation system and the possibility to perform a pre-operatory embolization lead to a change in the management of JNA now may be considered for endoscopic sinus-surgery removal.